Pengelolaan Lahan Akresi Desa Pambang Pesisir, Pulau Bengkalis, Provinsi Riau - Miswadi Miswadi; Romie Jhonnerie; Eko Prianto (Dinamika Lingkungan Indonesia, 2020)
The breakwater construction to overcome abrasion at Pambang Pesisir has resulted in the formation of land accretion which expanded the coastal land and giving rises to issues in public management. This research was aimed to formulate the alternative management of land accretion. A field survey and light unmanned aerial vehicle (drone) data acquisition were used to observe the accretion formed. Furthermore, Analytical Hierarchy Process (AHP) was used to generate the alternative managements of land accretion. Accretion land was estimated around 80,359.4 m2and based on coastal area protection, living creature’s habitat, fisheries resources, tourism and business development benefit, social community supporting and sustainability of social interaction criteria’s, this area had great potential to be managed with use it for mangrove planting or rehabilitation sites in ecological land-based management.